3515 Readability of online patient education materials on gynecologic malignancies from major medical associations. (27th March 2019) - Samuel, David; Vilardo, Nicole; Isani, Sara; Gressel, Gregory
Abstract : OBJECTIVES/SPECIFIC AIMS: Patients are increasingly using online materials to learn about gynecologic cancer. Recent studies demonstrate that 85-96% of patients with a gynecologic malignancy utilize the Internet as a health resource. Providers can refer patients to educational materials produced by major medical associations available on their websites. However, patient educational materials (PEMs) published by professional organizations from other surgical specialties have been shown to be difficult to read for the average American. The NIH and AMA recommend that PEMs be written between a sixth and eighth grade reading level. In this study, we assess the readability of online PEMs on gynecologic cancer published by major medical associations. METHODS/STUDY POPULATION: Seven national medical association websites with PEMs on gynecologic malignancy were surveyed: American College of Obstetricians and Gynecologists, Center for Disease Control, Foundation for Women's Cancer, National Cancer Institute, National Cervical Cancer Coalition, National Ovarian Cancer Coalition, and Society of Gynecologic Oncology. Online PEMs were identified and analyzed using five validated readability indices. One-way ANOVA and Tukey's test were performed to detect differences in readability between publishers. RESULTS/ANTICIPATED RESULTS: Two hundred and thirty PEMs were included in this analysis. Mean readability grade levels with standard deviation were: 11.3 (2.8) for Coleman-Liau index; 11.8 (3.2) for Flesch-Kincaid; 11.1 (1.2) for FORCAST formula; 12.5 (2.7) for Gunning FOG formula; 12.1 (2.6) for New Dale-Chall formula; and 13.5 (2.5) for SMOG formula. Overall, PEMs were written at a mean 12 th grade reading level. Only 4.3% of articles were written at an 8 th grade reading level or below. ANOVA demonstrated a significant difference in readability between publishing associations (p<0.01). PEMs from the Center for Disease Control had a mean 10 th grade reading level and were significantly lower than all other organizations. PEMs from The Foundation for Women's Cancer had a mean 13 th grade reading level and were significantly higher than most other organizations. DISCUSSION/SIGNIFICANCE OF IMPACT: Gynecologic oncology PEMs available from major medical association are written well above the recommended sixth to eight grade reading level. Simplifying PEMs may improve patient understanding of their disease and facilitate physician-patient communication.